THE EFFECT OF AUTHENTIC MATERIALS ON STUDENTS’ LISTENING PROCEDURAL TEXT ABILITY OF THE 2018/2019 NINTH YEAR STUDENTS AT SMP SWASTA DEWANTARA PUTRA SEBERTUNG - Ummi Umara (STKIP Budidaya Binjai, 2018)
BSTRACTThe study deals with an experimental research design which seeks for the effect of authentic materials on students’ listening procedural text ability. The problems that had been identified by the writer are including the students have many difficulties in learning English, such as understanding the listening lesson especially for procedure text, they are not able to achieve the standard valuing scores in listening lesson, lack of vocabulary of the students makes them feel so confused to understand the whole contents of the text, the learning materials are not in accordance with natural conditions and environment of the students, the instructional media cannot be used to motivate the students to improve their English listening, and the strategy implemented in teaching procedure text by the teacher is undrilled to subject later. 70 students at the ninth year students at SMP Swasta Dewantara Putra Sebertung in academic year of 2018/2019 are taken as the subject of the study. Listening test is used to obtain the data on the variable. The final data then is analyzed by using technique of t-test analysis. The result shows that coefficient of tcounted (2.15) was greater than the ttable coefficient (1.68595). This means that there is the effect of authentic materials on students’ listening procedural text ability of the 2018/2019 ninth year students at SMP Swasta Dewantara Putra Sebertung. Therefore, the hypothesis of the study is accepted.Keywords: Authentic Materials, Procedure Text, Listening Ability